Entepreneur Leadership, Competency, Knowladge Sharing terhadap Employee Performance: Study Pada IKM Pia Warurejo - Rina Agustin; Rifdah Abadiyah; Dewi Andriani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to describe and analyze the influence of Entepreneur Leadership, Competency, Knowledge Sharing variables on employee performance at IKM Pia Warurejo. In this research conducted using quantitative research methods, data collection is distributed through questionnaire /questionnaires, with samples using Random Sampling, where there are 108 respondents who are employee performance at IKM Pia Warurejo. The data analysis uses discriminant validity testing techniques, discriminant reliability, and hypothesis testing using the R test, F test, Q test. The data processing uses Smart PLS 4.0, the results of this research prove that first, Entrepreneurial Leadership has a significant influence on employee performance variables, second, Competence has a significant influence on employee performance variables, third, Knowledge Sharing has a significant influence on variables on employee performance.